Apakah Gosip Bisa Menjadi Kontrol Sosial? - Eko A Meinarno; Sunu Bagaskara; Mely Putri Kurniati Rosalina (Universitas Muria Kudus, 2011)
This study set out in the social life of the people of Indonesia. This issue is all about gossip as social control. If all this gossip to talk bad about as far as is known, then the Foster (2004) explains that one function of gossip is to influence people. One form that seems extreme is social control. The existence of social control are expected to achieve harmony in social life.In the current study focused on adolescents. In the adolescent phase of this development has wider social life and diverse. Patterns of friendship that extends also part of one's youth. Another important point is very sensitive to adolescents evaluative information against him. Thus gossip as a tool for social control could be the entrance to evaluate the adolescents in their everyday lives. R e s e a r c h e r s t a k e a s a m p l e o f approximately 250 adolescents randomly sampling with this type of random sampling. The proportion of men and women equally, the median age was 18.58 years (SD = 1.79). In this study used self-report measure of modality. Subtest function measurement using gossip as a tool to influence others from scale measuring GFQ (questionnaire Gossip Foster), composed by Eric foster (2004). As a result, 55.2 per cent of participants of the important functions of gossip influence others. However, if both sexes were compared results were not found substantial differences (though the average higher for women). Using these results can be expected that most gossip, but does not control or at least influence other people. It could, the supervisory functions should be something concrete, not just talk about word of mouth.